Worst Socioeconomic Outcome Still Increase the Prevalence of Dental Caries in Pre-Schools of a Municipality of Great Port in the South Brazil - Carolina Dea Bruzamolin; Daniella Cristina Gaio; Fernanda Mara de Paiva Bertoli; Juliana Feltrin de Souza; Estela Maris Losso; Eduardo Pizzatto; João Armando Brancher (Tehran University of Medical Sciences, 2022)
No Abstract